PENINGKATAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI SEKOLAH DASAR - Aprizan Aprizan; Abdulah Abdulah; Refril Dani; Randi Juanda (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This research started with the teacher not implementing learning methods that can make students active in group discussions; students have not been involved in group discussions, the learning methods used by teachers do not vary, and the learning process is still teacher-centred. This study aims to determine whether there is an increase in Citizenship Education learning outcomes on theme two, clean air for health, and sub-theme one, how the body processes clean air material for planting trees, using the cooperative learning model of the Student Team Achievement Division type in fifth-grade students at SDN 25/II Muara Bungo Bungo Dani District for the 2020/2021 school year? This type of research is Classroom Action Research, which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation of action, observation and analysis, and reflection. Based on the results of the research, it was found that the learning process of students in cycle I was in the fairly good category, while in cycle II, it was in the good category. This means that there is an increase in the learning process of students in a better direction. Meanwhile, the average score before the pre-cycle was 50.52%, with a completeness level of 49.38%. Then, in cycle I, the average value was 62.62% with a completeness level of 41.38%, and in cycle II, the average value was 76.52% with a completeness level of 76.45%. The average value of the pre-cycle, cycle I, and II shows an increase in learning outcomes.